1996
DOI: 10.1016/1011-1344(96)07342-3
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy: a promising new modality for the treatment of cancer

Abstract: The first reports on photodynamic therapy (PDT) date back to the 1970s. Since then, several thousands of patients, both with early stage and advanced stage solid tumours, have been treated with PDT and many claims have been made regarding its efficacy. Nevertheless, the therapy has not yet found general acceptance by oncologists. Therefore it seems legitimate to ask whether PDT can still be described as "'a promising new therapy in the treatment of cancer".Clinically, PDT has been mainly used for bladder cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
130
0
22

Year Published

1997
1997
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(152 citation statements)
references
References 73 publications
0
130
0
22
Order By: Relevance
“…PDT is being investigated for treatment of a variety of cancers. For recent reviews see Schuitmaker et al 66 Dougherty et al 67 and Chang and Bown. 68 PDT is also being investigated for use in non-malignant diseases such as rheumatoid arthritis 69 and the selective ablation of endometrial tissue.…”
Section: Clinical Applications Of Optical Spectroscopy For Cancer Thementioning
confidence: 99%
“…PDT is being investigated for treatment of a variety of cancers. For recent reviews see Schuitmaker et al 66 Dougherty et al 67 and Chang and Bown. 68 PDT is also being investigated for use in non-malignant diseases such as rheumatoid arthritis 69 and the selective ablation of endometrial tissue.…”
Section: Clinical Applications Of Optical Spectroscopy For Cancer Thementioning
confidence: 99%
“…Photodynamic therapy (PDT), also called photochemotherapy, is a new modality for the treatment of cancer [1][2][3] and a variety of nononcologic conditions [3][4][5][6][7]. PDT is based on administering a photosensitizer, which is preferentially retained in tumor (and other proliferating) tissue.…”
Section: Introductionmentioning
confidence: 99%
“…PDT is an FDA-approved form of cancer therapy involving the somewhat selective photosensitization of neoplastic cells, usually with porphyrins or porphyrin-like drugs. The delivery of a suitable light dose to photosensitized tissues can result in a highly-localized eradication of neoplastic lesions 9 with minimal damage to adjacent host tissues. Several groups have now reported that PDT can initiate a rapid apoptotic response.…”
Section: Introductionmentioning
confidence: 99%